2005
DOI: 10.1007/s11663-005-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the carbothermic reduction of chromite ores

Abstract: Experimental studies were carried out on the reducibility of two different chromite ores using different reducing carbonaceous reducing agents in the temperature range 1173 to 1573 K. "Friable lumpy" ores and "hard lumpy" ores were used in the experiments. Petroleum coke, devolatilized coke, (DVC) and graphite were used as reducing agents. It was found that iron was practically completely reduced before the commencement of the reduction of chromium in the ore. The reduction of iron was controlled by diffusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 8 publications
3
25
0
1
Order By: Relevance
“…As shown, the finer size fractions contain higher amounts of the gangue minerals, evidenced by the lower Cr 2 O 3 and higher SiO 2 concentrations. XRD (Rigaku D/MAX 2500, Rigaku Ltd., Tokyo, Japan) analysis of the 37-75 µm size fraction (Figure 1) indicates that the main gangue minerals are clinochlore (Mg,Fe) 5 Al(Si 3 Al)O 10 (OH) 8 , magnesite (MgCO 3 ), and phlogopite KMg 3 (Si 3 Al)O 10 (OH) 2 . Chromite size fraction of 180-300 µm has much less gangue, with only clinochlore identified by XRD (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown, the finer size fractions contain higher amounts of the gangue minerals, evidenced by the lower Cr 2 O 3 and higher SiO 2 concentrations. XRD (Rigaku D/MAX 2500, Rigaku Ltd., Tokyo, Japan) analysis of the 37-75 µm size fraction (Figure 1) indicates that the main gangue minerals are clinochlore (Mg,Fe) 5 Al(Si 3 Al)O 10 (OH) 8 , magnesite (MgCO 3 ), and phlogopite KMg 3 (Si 3 Al)O 10 (OH) 2 . Chromite size fraction of 180-300 µm has much less gangue, with only clinochlore identified by XRD (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the reduction of chromite directly by solid carbon (Equation (1)), chromite can also be reduced by gaseous CO forming CO2 (Equation (4)), resulting in the evolution of minor amounts of CO2 at approximately 150 min when pellets were heated ( Figure 14). The CO2 can be further consumed by the Boudouard reaction, i.e., Equation (5). The absence of this minor CO2 peak when the powder sample was used ( Figure 14) strongly suggests that the Boudouard reaction was greatly promoted.…”
Section: Influence Of Pelletizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These together make carbon as a reducing agent more environmentally and economically attractive than silicon. Carbon was then selected as the main reducing agent for recovery the metals from the waste briquettes [13][14][15][16] .…”
Section: On Internal Eaf Smelt-reduction Of the Wastecarbon Briquettesmentioning
confidence: 99%
“…Dawson & Edwards (1986), Niayesh & Dippenaar (1992), Xiao et al (2004), Chakraborty et al (2005) and Zhao & Hayes (2010), the influece of the electric current on the reduction reactions is usually omitted as anything else but a heat source . Experiments conducted by Rousu et al (2010) indicated the enhancing effect of electric current on the reduction reactions thus giving a little information concerning the dependancies between the current and the reactions.…”
Section: Submerged Arc Furnace Safmentioning
confidence: 99%